İlkokul 3. ve 4. Sınıf Öğrencilerinin Çocuk Hakları Konusundaki Bilinç Düzeylerinin Belirlenmesi: Bir Ölçek Geliştirme Çalışması - Akgül, Mehmet Şaban; Çağlayan, Kaya Tuncer (Muş Alparslan Üniversitesi, 2019)
Inthis study, it was aimed to improve a reliable and a valid scale for measuringthe consciousness levels of 3rd and 4th grade primary school student aboutchild rights. This research is a scale improvement study and in the surveyprocess scanning method, one of the quantitive research methods, was used. Thescale improved under the scope of research is consisted of 3 factors and 18items. During the research process we studied with 501 primary school studentsof 3rd and 4th grades in 2017 – 2018 academic year in the Tokat province-wide.At the validity stage; content validity, face validity and construct validitywere investigated. At the reliability stage; coefficient of internalconsistence, 27% subgroup supergroup averages were measured and relationshipsbetween factors and 27% subgroup supergroup relationships were of scale itemswere examined. At the end of the research a scale, whose validity andreliability were validated, with 3 subgroup and 18 items aimed at ‘Thedefinition of ideas of3rd and 4th grade primary school student about childrights’ developed.

Buçalışmada, ilkokul 3. ve 4. Sınıf öğrencilerinin çocuk hakları konusundakibilinç düzeylerini ölçmeye yönelik geçerli ve güvenilir bir ölçek geliştirmekamaçlanmıştır. Bu araştırma bir ölçek geliştirme çalışması olup, araştırmasürecinde nicel araştırma yöntemlerinden olan tarama yöntemi kullanılmıştır.Araştırma kapsamında geliştirilen ölçek 3 faktör ve 18 maddeden oluşmaktadır.Araştırma sırasında 2017-2018 eğitim öğretim yılında Tokat il genelindekiçeşitli okullarda 3. ve 4. Sınıfta öğrenim gören 501 öğrenci ile çalışılmıştır.Geçerlik aşamasında; kapsam, görünüş ve yapı geçerliği incelenmiştir.Güvenirlik aşamasında; iç tutarlık katsayısı, %27’lik alt grup üst gruportalamaları hesaplanmış olup, faktörler arası ilişkiler ve ölçek maddelerinin%27 lik alt grup üst grup ilişkileri incelenmiştir. Araştırma sonucundageçerliliği ve güvenirliği sağlanmış “İlkokul 3. ve 4. Sınıf ÖğrencilerininÇocuk Hakları Konusundaki Görüşlerinin Belirlemesi” ne yönelik 3 alt boyutlu ve18 maddeye sahip bir ölçek geliştirilmiştir.
The Definition of the Consciousness Level of 3rd and 4th Grade Primary School Studens About Child Rights: a Scale Development Work
anemon
Keywords: Child Rights; Scale Development; Primary School; çocuk hakları; ölçek geliştirme; ilkokul